The Effectiveness of Duloxetine for Knee Osteoarthritis: An Overview of Systematic Reviews - Zhou, Qinxin; Chen, Jixin; Yu, Weijie; Yang, Kun; Guo, Tianci; Niu, Puyu; Ye, Yuntian; Liu, Aifeng (Frontiers in Physiology, 2022)
Background: Knee osteoarthritis (KOA) has become a public health problem. Several systematic reviews (SRs) have reported that duloxetine may be an effective treatment for improving pain and depressive symptoms in patients with KOA. Aim: To evaluate the available results and provide scientific evidence for the efficacy and safety of duloxetine for KOA. Methods: A comprehensive search strategy was conducted across eight databases from inception to 31 December 2021. Two researchers independently selected eligible studies, collected data and evaluated those included SRs’ quality. For assessing methodological quality, the Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR 2) was employed. Risk of Bias in Systematic Reviews (ROBIS) was used to assess the risk of bias. Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) was utilized for assessing reporting quality. In addition, the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to determine primary outcome indicators’ evidence quality. Results: Totally 6 SRs were contained in this overview. After assessment based on AMSTAR 2, ROBIS, and PRISMA, unsatisfactory results in terms of methodological quality, risk of bias as well as reporting quality, were obtained. Limitations included a search of grey literature, the reasons for selecting the study type, an excluded study list and the specific reasons, reporting bias assessment, and reporting of potential sources of conflict of interest. According to the GRADE results, the evidence quality was high in 0, moderate in 5, low in 19, and very low in 36. Limitations were the most commonly downgraded factor, followed by publication bias and inconsistency. Conclusion: Duloxetine may be an effective treatment for improving pain and depressive symptoms in KOA patients with acceptable adverse events. However, due to the low quality of the available evidence, the original study design and the quality of evidence from SRs should be further improved, so as to provide strong scientific evidence for definitive conclusions. Systematic Review Registration: PROSPERO; (http://www.crd.york.ac.uk/PROSPERO/), identifier (CRD42021289823).